Improved Collaboration and Learning Outcomes Theme VII Sub-Theme 3 Through the Discovery Learning Learning Model for Grade VI Students of SD Negeri 2 Samigaluh 2021/2022 Academic Year - Srini (Universitas Islam Indonesia, 2023)
This study aims to improve collaboration skills and learning outcomes of students in Theme VII Sub-Theme 3 using the discovery learning model for class VI students at SD Negeri 2 Samigaluh in the 2021/2022 academic year. This type of research is a Classroom Action Research (CAR) for 2 cycles, each cycle consisting of 2 meetings. The subjects in this study were class VI students at SD Negeri 2 Samigaluh for the 2021/2022 academic year, with a total of 11 students consisting of 5 boys and 6 girls. Data collection techniques in this study were based on observation results. The results of this study indicate an increase in students' collaboration skills, namely in the first cycle the average value was 18.18% while in the second cycle the average value was 86.37%. The results of the research data on student learning outcomes also showed an increase, this is known from the average value in cycle I of 68.18%, while in cycle II an average value of 95.45%. This shows that the application of discovery learning models can improve collaboration and learning outcomes of class VI students at SD Negeri 2 Samigaluh on theme VII sub-theme 3.